2017
DOI: 10.1139/cjss-2017-0037
|View full text |Cite
|
Sign up to set email alerts
|

Carbon, nitrogen and phosphorus release from peat and forest floor-based cover soils used during oil sands reclamation

Abstract: Reclamation practices in the oil sands region of Alberta involve the reconstruction of soil profiles using a combination of salvaged mineral substrates and organic-matter-rich surface materials, including peatmineral mix (PM) and forest floor -mineral mix (FFM). The successful re-establishment of vegetation on reclaimed sites is for a large part dependent on the nutrients these materials can provide. Hence, the overall objective of this study was to compare carbon (C), nitrogen (N), and phosphorus (P) release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 28 publications
4
18
0
Order By: Relevance
“…Studies on peat soils (Kaal et al, 2007; Barkovskii et al, 2009; Perez‐Rodriguez and Cortizas, 2014) showed that polysaccharides decrease exponentially with depth and the labile compounds are more degraded on surface, whereas more recalcitrant substrates are found at greater depth. Carbohydrates and carboxylic acids were the dominant drivers of nutrient bioavailability in fPMM, which also corroborates the chemical characterization of PMM done by Béasse et al (2015) and Quideau et al (2017), indicating the presence of labile short chain C substrates. Major drivers of nutrients in FFMM also shifted from mostly carbohydrates in the fresh to mostly amino acids in the stockpiled soils.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Studies on peat soils (Kaal et al, 2007; Barkovskii et al, 2009; Perez‐Rodriguez and Cortizas, 2014) showed that polysaccharides decrease exponentially with depth and the labile compounds are more degraded on surface, whereas more recalcitrant substrates are found at greater depth. Carbohydrates and carboxylic acids were the dominant drivers of nutrient bioavailability in fPMM, which also corroborates the chemical characterization of PMM done by Béasse et al (2015) and Quideau et al (2017), indicating the presence of labile short chain C substrates. Major drivers of nutrients in FFMM also shifted from mostly carbohydrates in the fresh to mostly amino acids in the stockpiled soils.…”
Section: Discussionsupporting
confidence: 89%
“…The current study also demonstrated the use of simple microbial functional profiles (CLPP) in assessing the effects of operational management practices on soil quality and the findings are comparable to other studies that used more sophisticated methods (e.g., Béasse et al, 2015; Quideau et al, 2017). Similar approach can be adopted for routine soil measurements and monitoring changes in the reclaimed and other disturbed sites.…”
Section: Conclusion and Operational Implicationssupporting
confidence: 84%
See 1 more Smart Citation
“…MacKenzie [16] found that stockpiling FFMM increased available phosphorus and potassium and did not substantially change total percent nitrogen or organic matter. In our study, the greater amount of phosphorus and potassium in stockpiled FFMM may partly be because the soil was obtained from a potentially more nutrient-rich site than the other soils, potential nutrient flush from decomposing or decomposed forest floor material [19], and the…”
Section: Discussionmentioning
confidence: 86%
“…Results from stockpiling peat and peat mineral mixes in Alberta also suggest that stored peat nutrient contents are similar to undisturbed peat, and changes in nutrient or organic carbon levels may be due to admixing with mineral soil [18]. Because the successful re-establishment of vegetation on FFMM and PMM is largely dependent on the nutrients these materials can provide [19], it is important to assess the nutrient status of stockpiled reclamation soils as this would provide a better indication of their suitability for forest-land reclamation than the duration of soil storage.…”
Section: Introductionmentioning
confidence: 99%